Treatment of Nasal Aging and Possible Long-term Nasal Enhancement with Fat Using Injectable Tissue Replacement. Issue 5 (May 2019) - Cohen, Steven R.; Womack, Hayley A.; Hauch, Adam T.; Delaunay, Flore; Trivisonno, Angelo
Abstract : Summary: This article addresses nasal aging using a minimally invasive procedure with an algorithm that includes the diagnosis of a patient's nose within the context of the individual's facial anatomy. Pyriform augmentation for the elevation of tip projection and columellar strutting with injectable fat are, to our knowledge, applied for the first time as important steps in minimally invasive rhinoplasties. This procedure offers patients with more subtle nasal changes with aging or other causes to be treated with potentially long-lasting improvements, which can be easily retreated. New techniques using injectable liquid cartilage grafts are being explored.